Systematic review of the literature on quilombola education in the context of ethnic-racial relations (Research, Society and Development, 2024)
This article has attempted to analyze the impact of Law 10.678 of 2003, and there is a need to deepen this topic, which is very relevant to the school environment, even though more than 20 years have passed since the law was passed. A movement to decolonize curricula has begun in the education field, which is already reflected in the Affirmative Action movement proposed by the federal government. The purpose of this study was to conduct a systematic review of the literature to gather information about quilombola education in the context of ethnic-racial relations and to identify possible avenues for future research in this area. This is a systematic, exploratory, and qualitative literature review with the goal of summarizing work on quilombola education over the past five years, a period that encompasses recent educational policies on the topic. The results suggest that public policy is moving forward, as there is not much reflection on the issue. Another detail that stands out in this systematic review is the absence of works in the field of artistic expression and language, and thus the lack of publications in other fields.